(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This scientific article notes the formation of the state as a full-fledged participant in international trade relations, the development of partnership trade relations, as well as the essence of agreements on tariffs and trade and rules of origin of goods. This paper also discusses methods for identifying the origin of goods and possible problems with these agreements.